'Cash waqf' and Islamic microfinance: untapped economic opportunities - Md Saad, Norma; Anuar, Azizah (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2009)
The success of microfinance programmes in alleviating poverty in many countries has spurred the development of faith-based microfinance institutions. Muslims have combined certain elements in Islamic finance and microfinance to create a new programme called ‘Islamic microfinance’ and use it as a tool to fight poverty in their community. Even though microfinance is proven successful in fighting poverty, current microfinance practised by commercial banks in Malaysia has several shortcomings. Current weaknesses include stringent credit evaluation and missing the real target group, i.e., the poor and the needy. Furthermore, the mode of financing is mostly personal loan using bay‘ al-‘īnah, whereby the use of the loan is to fulfil personal consumption instead of income-generating activities. Given these shortcomings, the article explores the possibility of using ‘cash waqf’ as a new source of funding for Islamic microfinance and proposes a new concept and application of Islamic microfinance so that it is truly in line with the Islamic spirit of microfinance. It is hoped that with this new concept and application of Islamic microfinance, the use of microfinance genuinely caters for the needs of the poor as well as generating socio-economic growth of the Muslim ummah.